Introductory econometrics : a modern approach - Wooldridge, Jeffrey M., 1960- (Cengage, 2025)
Introductory Econometrics: A Modern Approach provides students with an understanding of how econometrics can answer questions in business, policy evaluation, and forecasting. Wooldridge’s practical approach emphasizes real-world applications and helps students develop the skills to interpret and apply econometric results. The 8th edition includes refined coverage of recent developments in the field, new examples, and online resources for hands-on practice.